2013
DOI: 10.1017/s0022215113000509
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life measures in otitis media

Abstract: Disabling hearing impairment is the world's most common disability. Traditionally, hearing levels measured by pure tone audiometry have been used to define and quantify hearing loss. The effects of disabling hearing loss on patients' quality of life can be profound, and audiometric data alone may not correlate with quality of life measures. Generic measures of quality of life can be used to compare different diseases, and as such are useful in resource allocation and burden of disease studies. Their disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Therefore, it is important to have effective measures of quality of life (QoL) and health status to evaluate the burden of disease and effectiveness of treatments. A number of effective instruments exist for use in high‐income countries, which are reviewed here . However, the availability of effective instruments for use in low‐income countries is limited .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to have effective measures of quality of life (QoL) and health status to evaluate the burden of disease and effectiveness of treatments. A number of effective instruments exist for use in high‐income countries, which are reviewed here . However, the availability of effective instruments for use in low‐income countries is limited .…”
Section: Introductionmentioning
confidence: 99%
“…A number of effective instruments exist for use in high‐income countries, which are reviewed here . However, the availability of effective instruments for use in low‐income countries is limited . The use of instruments developed in high‐income countries is difficult as they are often not available in multiple languages, and the items are not always applicable to low‐income nations.…”
Section: Introductionmentioning
confidence: 99%
“…7 The principle instrument used was the Glasgow Benefit Inventory. 8 Interestingly, they found that mastoid surgery for chronic otitis media in most patients did not produce an increase in QoL. This finding differs from a study in a low-income country, which showed significant improvement in QoL in patients who underwent middle-ear surgery.…”
Section: Targets and Outcomesmentioning
confidence: 73%
“…Therefore, these data are useful as a complement to the previously reported hearing data and surgical outcome. The GBI is a non-disease-specific tool for the measurement of HRQoL in contrast to, for example, the CES, but to its advantage, it is possible to make comparisons between different interventions [23].…”
Section: Strengths and Advantages Of The Studymentioning
confidence: 99%